2013
DOI: 10.1242/dev.093641
|View full text |Cite
|
Sign up to set email alerts
|

Lgr4-mediated Wnt/β-catenin signaling in peritubular myoid cells is essential for spermatogenesis

Abstract: SUMMARYPeritubular myoid cells (PMCs) are myofibroblast-like cells that surround the seminiferous tubules and play essential roles in male fertility. How these cells modulate spermatogenesis and the signaling pathways that are involved are largely unknown. Here we report that Lgr4 is selectively expressed in mouse PMCs in the testes, and loss of Lgr4 leads to germ cells arresting at meiosis I and then undergoing apoptosis. In PMCs of Lgr4 mutant mice, the expression of androgen receptor, alpha-smooth muscle ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…Most animals that survived until birth died in the first days after Kato et al 2006). Neonatal null mice displayed a variety of abnormalities: male infertility Hoshii et al 2007;Li et al 2010;Mohri et al 2010;Qian et al 2013), impaired prostate development , defective uterine development (Sone et al 2013), delayed development of mammary ducts Wang et al 2013c), severe abnormalities in the anterior segment of the eye (Song et al 2008;Weng et al 2008), abnormal erythropoiesis (Song et al 2008), defective osteoblast differentiation (Luo et al 2009), renal defects (Kato et al 2006;Mohri et al 2011), defective development of the gall bladder (Yamashita et al 2009), eye-open phenotype (Kato et al 2007;Jin et al 2008), and abnormalities in hair follicle development (Mohri et al 2008). In addition, ablation of Lgr4 in mice appears to promote the white-to-brown fat switch, leading to energy expenditure (Wang et al 2013b).…”
Section: Lgr5 Marks Intestinal Stem Cellsmentioning
confidence: 99%
“…Most animals that survived until birth died in the first days after Kato et al 2006). Neonatal null mice displayed a variety of abnormalities: male infertility Hoshii et al 2007;Li et al 2010;Mohri et al 2010;Qian et al 2013), impaired prostate development , defective uterine development (Sone et al 2013), delayed development of mammary ducts Wang et al 2013c), severe abnormalities in the anterior segment of the eye (Song et al 2008;Weng et al 2008), abnormal erythropoiesis (Song et al 2008), defective osteoblast differentiation (Luo et al 2009), renal defects (Kato et al 2006;Mohri et al 2011), defective development of the gall bladder (Yamashita et al 2009), eye-open phenotype (Kato et al 2007;Jin et al 2008), and abnormalities in hair follicle development (Mohri et al 2008). In addition, ablation of Lgr4 in mice appears to promote the white-to-brown fat switch, leading to energy expenditure (Wang et al 2013b).…”
Section: Lgr5 Marks Intestinal Stem Cellsmentioning
confidence: 99%
“…Lgr4 gene deletion have been shown to cause developmental defects in multiple organs, including male reproductive tracts, spermatogenesis, bone formation and hair follicle development, as well as reduced embryonic growth (Mazerbourg et al, 2004;Mohri et al, 2008;Luo et al, 2009;Li et al, 2010;Qian et al, 2013). In addition, recent studies identify members of the R-spondin family as ligands for LGR4, directly linking this GPCR to the Wnt/β-catenin signaling (de Lau et al, 2011;Glinka et al, …”
Section: Introductionmentioning
confidence: 99%
“…Considering that some interneurons in the molecular layer also express Lgr4, the upstream signaling of PC is also worth investigating. One candidate of Lgr4 downstream signaling is the Wnt/␤-catenin signaling, which is triggered by R-spondin proteins in different organs (19,23,24). The Wnt/␤-catenin signaling has also been shown to play an important role in the development of the central nervous system (47,48), but its function in cerebellar development is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Using a gene trap strategy, we generated Lgr4 hypomorphic mice with low viability (60% mortality rate) but a normal life span. Our previous studies have demonstrated that Lgr4 plays important roles in various organs, including eye (15), bone (22), blood (16,17), intestine (23), testis (24), mammary gland (25), and prostate (26). Although a previous report showed strong expression in neurons of many brain regions, especially in cerebellar PCs (27), the role of Lgr4 in the central nervous system has not been studied.…”
mentioning
confidence: 99%